Avicenna's Approach to Health: A Reciprocal Interaction Between Medicine and Islamic Philosophy - Zahabi, Seyed Abbas (Journal of religion and health, 2019)
This paper elucidates how Islamic philosophy is associated with health and illness. Avicenna (980-1037) as the most important physician and philosopher in the Islamic world has undoubtedly affected various fields of thought and science in Islamic civilization. The basis and infrastructure of his understanding of medicine derive from his philosophical and religious views. According to Avicenna, the soul and body are two intertwined substances from which all human beings are composed. This reciprocal interaction between soul and body is essential in analyzing his medical concepts related to "health" and "sickness." Other than soul, he believes in spirit which is originally a religious concept that he interprets. Avicenna distinguishes between soul and spirit ( rūḥ) and poses that, as an ethereal volatile substance, the spirit is a mediator between soul and body. He also proposes a hierarchical system of spirit through which he illustrates a special type which is called "Rūḥ Bukhārī" (= RB). Faculties of the soul firstly penetrate into this type of spirit and then enter the body's organs. Consequently, health and sickness are interpreted through the terms and conditions of RB.